Comparative Analysis of Engineering and Art Learner’s Readiness towards the use of E-Portfolio - Bahsan, Rosnadiah; Nor Azlan Mohamad, Syamsul; Nur Dini Mahazan, Siti (International Journal of Engineering and Technology, 2018)
This paper presents the comparative analysis learners’ readiness among Engineering and Art students in higher learning institution. The study was focused on examining 120 students from Engineering and Art cluster to practice e-Portfolio for their courses. The pilot study was tested the reliability coefficient with Cronbach’s alpha (α) of 0.825. The survey of learner readiness was divided into five constructs to assess the readiness towards using e-portfolio for future assessment purposes. The finding was concluded that the students are indeed ready to use e-Portfolio as an appropriate platform for integrative learning. The use of e-Portfolio will broaden the possibility to promote outcome-based education and constructive alignment which encompassed practical skills such as critical thinking, problem solving, information management and lifelong skills. The preliminary study proved that e-Portfolio is beneficial to students, faculty and stakeholders.